FRAMING ANALYSIS OF ANIES BASWEDAN'S IMAGE POST DECLARATION AS CAPRES 2024 AT CNNINDONESIA.COM - Nilamaida Nilamaida; Solihah Titin Sumanti (KABILAH : Journal of Social Community, 2022)
Abstract: After the declaration as a 2024 presidential candidate by one of the parties, Anies Baswedan's name became inseparable from the media spotlight and even became a public discussion. Anies' presence which is in the spotlight from various media can shape Anies' political image which cannot be separated from the role of the media in constructing news discourse. Image is the impression that someone has of something, in this case a political figure. The purpose of this research is to find out how CNNIndonesia.com's framing affects Anies Baswedan's political image after his declaration as a presidential candidate for 2024. The analytical method used is a qualitative approach using Robert N. Entman's framing analysis technique with the object of analysis in six news stories from 3-8 October 2022 on CNNIndonesia .com. The results obtained from this study show that, first of all, Anies' image is constructed as a leader who must focus on his position and work. The second news framing Anies' positive image as a leader who is able to carry out two mandates at once and not shirk responsibility. The third news framing Anies as a leader who is clean, honest and wise in dealing with problems. The fourth news framing Anies as a populist leader. The fifth news framing Anies as a political figure who still lacks support. The sixth news, framing Anies' image as a leader who is clean from corruption cases. Keywords: Frame Analysis, Image, Anies Baswedan, Cnnindonesia.Com